PERAN LINGKUNGAN SEKOLAH DALAM MENINGKATKAN KEPEDULIAN SISWA KRISTEN DI SMA NEGERI 3 SURAKARTA - Angger Kusuma Ningtias; Justin Niaga Siman Juntak (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe and analyze the role of the school environment in increasing the caring attitude of Christian students at SMA Negeri 3 Surakarta. Using a qualitative approach with a descriptive case study design, data were collected through non-participatory observation, semi-structured interviews with a Christian Religious Education teacher and twelve Christian students, and documentation. Data validation was carried out through source and method triangulation, while data analysis followed an interactive model consisting of data reduction, data display, and conclusion drawing. The results showed that the school environment plays a strategic role in shaping students' caring characters. This is evident through the role of teachers as role models, a positive school culture, and inclusive social interactions. Christian values of love serve as the spiritual foundation that motivates students to care for others. In addition, the synergy between families and churches reinforces the internalisation of these values. Despite facing challenges such as modern individualism and media social usage, social experiences through collaborative learning, extracurricular activities, and community service effectively transform the concept of love into concrete social actions.